Virtual reality system for baseball pitcher fatigue analysis and sport injury diagnosis - WANG, SHIU MIN; HSU, WEI LI (2023)
The invention discloses a virtual reality system for baseball pitcher fatigue analysis and sport injury diagnosis. A fatigue analysis module analyzes whether change in pitching movement of a baseball pitcher has reached a fatigue standard based on value of trajectory displacement change of a body centroid and value of joint angle change of a body joint of the baseball pitcher when pitching a ball. When the fatigue standard has been reached, a warning message indicating that the change in pitching movement of the baseball pitcher has reached the fatigue standard will be displayed on a virtual reality device. Next, a sport injury diagnosis module uses sport injury diagnosis technology or physical therapy knowledge to determine whether the change in pitching movement of the baseball pitcher will cause sport injury to the baseball pitcher or whether there is a risk of sport injury. If yes, the sport injury diagnosis module provides sport injury diagnosis information of the baseball pitcher based on the value of t